Human rights in the European Union constitution - Nastić Maja (Međunarodni Problemi, 2006)
The paper deals with the innovations the Treaty Establishing a Constitution for Europe brings into the field of human rights. One of them is incorporation of the Charter of Fundamental Rights into the very Constitution. In this way, a political declaration adopted in Nice has become a legal document, achieving also constituionalisation of fundamental rights at the Union level. Secondly, there is an explicit possibility for the EU to accede the European Convention for the Protection of Human Rights and Fundamental Freedoms. Within that context the author considers the relationship between the Charter of Human Rights and the European Convention, as well as the relationship between the two courts: the European Court of Human Rights and the European Court of Justice.